2023
DOI: 10.2169/internalmedicine.1612-23
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Juvenile Polyposis with Intramucosal Cancer Diagnosed by Magnifying Endoscopy with Narrow-band Imaging

Abstract: Although gastric juvenile polyposis (GJP) often coexists with gastric cancer, a preoperative accurate diagnosis is still difficult to obtain. A 70-year-old woman was referred for epigastralgia and anemia. Esophagogastroduodenoscopy with a conventional endoscope showed numerous gastric polyps with no cancerous findings. Magnifying endoscopy with narrow-band imaging (M-NBI) showed cancerous findings, and a target biopsy revealed adenocarcinoma. Histopathological findings after endoscopic resection confirmed a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…However, because GJP is accompanied by numerous gastric polyps, it can be difficult to detect early-stage cancer or dysplasia by conventional endoscopy alone. Utsunomiya et al ( 5 ) reported a case of GJP with intramucosal gastric cancer that was diagnosed by a target biopsy using magnifying endoscopy (ME). This case report highlights the importance of utilizing advanced diagnostic techniques, such as ME, in the evaluation of gastrointestinal polyposis.…”
mentioning
confidence: 99%
“…However, because GJP is accompanied by numerous gastric polyps, it can be difficult to detect early-stage cancer or dysplasia by conventional endoscopy alone. Utsunomiya et al ( 5 ) reported a case of GJP with intramucosal gastric cancer that was diagnosed by a target biopsy using magnifying endoscopy (ME). This case report highlights the importance of utilizing advanced diagnostic techniques, such as ME, in the evaluation of gastrointestinal polyposis.…”
mentioning
confidence: 99%